The Effect Of Profitability, Financial Distress, Company Operational Complexity And Company Size On Audit Delay In Mining Sector Companies - Sherly Heriyanti; Sri Rahayu; Wiwik Tiswiyanti (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines how profitability, financial distress, operational complexity, and company size influence audit delay, analyzed in non-financial companies listed on the Indonesia Stock Exchange between 2021 and 2023. Audit delay is a critical issue because it impacts the timeliness of financial information delivery needed by stakeholders in decision-making. Timeliness of reporting reflects the level of transparency and accountability of a company to the public. Profitability reflects a company's ability to generate profits, financial distress indicates the potential risk of default, operational complexity relates to the operational structure and number of subsidiaries, while company size reflects the extent of resources and reporting systems. A purposive sampling method was used to obtain a sample of 228 observational data from 57 companies over three years. Secondary data obtained from company annual reports were collected through documentation methods. SPSS 29 was used to conduct regression analysis on the obtained data. This research is expected to provide additional insights for academics, auditors, and regulators in understanding the factors influencing audit delay and encouraging the creation of a more efficient and accountable audit process.